Dampak Inflasi Dan Nilai Tukar Mata Uang Pada Perkembangan Pasar Uang Syariah Di Indonesia - shofiyati, hidayatis; tofa, mus (Jurnal Ilmiah Ekonomi Islam, 2023)
Abstract This study aims to see and examine the impact of inflation and rupiah exchange on the effect of inflation on the development of the Islamic money market, especially in Indonesia. Inflation is said to be the main review in interest rate development, where inflation has an impact on the Islamic money market by having a positive and negative impact. Judging from today's life, it can be clearly understood that inflation is the current trend of rising product prices. The existence of price increases or inflation can override the purchasing power of the public and have a major effect on the level of financing of fund deposits. In addition to inflation which is compressed on the development of the Islamic money market, there is also the exchange of rupiah currency which has a major impact on the Islamic money market. The rupiah exchange rate is the value of one rupiah currency with the transfer of money to another country's currency. The impact of the currency exchange rate on the economy can be seen from the size of financing and prices arising from changes in the currency exchange rate itself. The management of currency exchange rates that influence the development of the Islamic money market will be determined by the exchange rate system regulated by each country, especially Indonesia. Therefore, the Islamic money market can develop due to the impact of inflation and currency exchange rates. The development of the Islamic money market, where when interpreting a money according to sharia is money as a tool to gain memory or additional economic falue. Money can grow if it is pooled in a real economic activity Keywords : Inflation, Currency Exchange Rates, Islamic Money Market